Pengembangan dan Inovasi Kurikulum di TPA/MDA dalam Menghadapi Tantangan Era Digital - Eviyarman; Iswantir (Lembaga Yasin AlSys, 2026)
Qur’anic Education Centers (TPA) and Madrasah Diniyah Awaliyah (MDA) are non-formal Islamic educational institutions that play an important role in shaping character, instilling Islamic values, and developing school-age children’s ability to read the Qur’an. However, developments in information technology, globalization, and social change require curriculum renewal to ensure that TPA/MDA education remains relevant to students’ needs. This study aims to analyze the concept of TPA/MDA curriculum development, the urgency of curriculum innovation, the forms of innovation that can be implemented, and the supporting and inhibiting factors affecting its implementation. This study employed a library research method by examining books, scientific journal articles, educational regulations, and relevant previous studies. The results show that TPA/MDA curriculum development needs to be implemented systematically through the stages of planning, implementation, evaluation, and continuous development. Curriculum innovation can be realized through the integration of character education, digital literacy, project-based learning, experiential learning, the strengthening of religious moderation, and the use of digital technology in the learning process. The implementation of an innovative curriculum is supported by teacher competence, the availability of facilities and infrastructure, parental involvement, and the commitment of institutional administrators, whereas limitations in these aspects may hinder its implementation. This study confirms that collaboration among all stakeholders is necessary to develop a TPA/MDA curriculum that is adaptive and relevant to the needs of twenty-first-century students without neglecting Islamic values as the primary foundation of education. These findings contribute to the conceptual development of the curriculum for non-formal Islamic education and provide practical guidance for TPA/MDA administrators in designing contextual and sustainable learning innovations.